Automated Model Generation and Observer Design for Interconnected Systems A Port-Hamiltonian Approach - Pfeifer, Martin (Karlsruher Beiträge zur Regelungs- und Steuerungstechnik, 2022)
This work addresses the automated generation of physical-based models and model-based observers. We develop port-Hamiltonian methods, which for the first time allow a complete and consistent automation of these two processes for a large class of interconnected systems.